2021
DOI: 10.3390/nu13082776
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Supplement Intake in Recreational Endurance Runners—Results from the NURMI Study (Step 2)

Abstract: It has been well-documented that female and male athletes differ in many physiological and psychological characteristics related to endurance performance. This sex-based difference appears to be associated with their nutritional demands including the patterns of supplement intake. However, there is a paucity of research addressing the sex differences in supplement intake amongst distance runners. The present study aimed to investigate and compare supplement intake between female and male distance runners (10 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 85 publications
1
28
0
1
Order By: Relevance
“…Nutrient/nutritional concerns might be more critical for endurance athletes who are known to have a higher risk of low energy availability [46], such as those who follow specific kinds of diets (e.g., plant-based diets) and particularly when the diet is not appropriately planned [47]. Findings from our laboratory indicate that vegan runners have a higher intake of dietary supplements to meet their nutritional requirements [48], without sex-specific association [49]. At the same time, it has also been shown that dietary needs can be translated appropriately to a well-planned personalized diet and even ultra-endurance challenges (e.g., mountain bike race) can be successfully completed following a vegan diet [50].…”
Section: Discussionmentioning
confidence: 77%
“…Nutrient/nutritional concerns might be more critical for endurance athletes who are known to have a higher risk of low energy availability [46], such as those who follow specific kinds of diets (e.g., plant-based diets) and particularly when the diet is not appropriately planned [47]. Findings from our laboratory indicate that vegan runners have a higher intake of dietary supplements to meet their nutritional requirements [48], without sex-specific association [49]. At the same time, it has also been shown that dietary needs can be translated appropriately to a well-planned personalized diet and even ultra-endurance challenges (e.g., mountain bike race) can be successfully completed following a vegan diet [50].…”
Section: Discussionmentioning
confidence: 77%
“…Reports from national dietary investigations on general populations of D-A-CH countries (including Germany, Austria, and Switzerland; home of the majority of participants) also show that sex is a remarkable contributor to dietary intake/patterns [64][65][66][67]. Dietary-related sex differences in endurance runners, however, cannot only be attributed to the patterns of supplement intake, as previously reported by the "NURMI Study" [68].…”
Section: Discussionmentioning
confidence: 78%
“…Compared with the highest rate of supplement intake reported by half-marathoners (16%), a recent study reported that 30% of female and 40.2% of male endurance runners consume supplements in order to enhance performance 72 . Although few studies have yet compared different groups of endurance runners regarding the patterns of supplement intake 73 , it has been well-documented that endurance athletes use supplements to a greater extent than non-endurance athletes 74 , probably due to the higher exercise-induced nutritional requirements associated with long-time training, competition, and recovery 75 . Reports from a recent study on elite track and field athletes indicated that distance runners have a significantly higher prevalence in supplemental micronutrient but not macronutrient intake when compared to runners in other track and field disciplines 76 .…”
Section: Discussionmentioning
confidence: 99%